Linking Phospho-Gonadotropin Regulated Testicular RNA Helicase (GRTH/DDX25) to Histone Ubiquitination and Acetylation Essential for Spermatid Development During Spermiogenesis - Kavarthapu, Raghuveer; Anbazhagan, Rajakumar; Sharma, Ashish K.; Shiloach, Joseph; Dufau, Maria L. (Frontiers in Cell and Developmental Biology, 2020)
GRTH/DDX25 is a testicular RNA helicase expressed in germ cells that plays a crucial role in completion of spermatogenesis. Previously, we demonstrated a missense mutation (R242H) of GRTH gene in Japanese infertile patients (5.8%) with non-obstructive azoospermia. This mutation upon expression in COS-1 cells revealed absence of the 61 kDa phosphorylated GRTH in cytoplasm and the presence of the 56 kDa non-phosphorylated GRTH in the nucleus. GRTH knock-in (KI) mice carrying the human GRTH (R242H) mutation, lack phosphorylated GRTH, and sperm due to failure of round spermatid elongation during spermiogenesis. To determine the impact of phosphorylated GRTH on molecular events/pathways participating in spermatid development during spermiogenesis, we analyzed transcriptome profiles obtained from RNA-Seq of germ cells from KI and WT mice. RNA-Seq analysis of 2624 differentially expressed genes revealed 1404 down-regulated and 1220 up-regulated genes in KI mice. Genes relevant to spermatogenesis, spermatid development and spermatid differentiation were significantly down-regulated. KEGG enrichment analysis showed genes related to ubiquitin-mediated proteolysis and protein processing in endoplasmic reticulum pathway genes were significantly down-regulated while the up-regulated genes were found to be involved in Focal adhesion and ECM-receptor interaction pathways. Real-Time PCR analysis confirmed considerable reduction in transcripts of ubiquitination related genes Ube2j1, Ube2k, Ube2w, Rnf8, Rnf133, Rnf138, Cul3 and increased expression of Ccnd2, Col1a, Lamb1, Cav1, Igf1, Itga9 mRNA’s in KI mice compared to WT. Also, marked reduction in protein expression of UBE2J1, RNF8, RNF138 (ubiquitination network), MOF (histone acetyltransferase), their modified Histone substrates (H2AUb, H2BUb) and H4Ac, H4K16Ac were observed in KI mice. GRTH-IP mRNA binding studies revealed that Rnf8 and Ube2J1 mRNAs from WT mice associated with GRTH protein and the binding is greatly impaired in the KI mice. Immunohistochemistry analysis showed significantly reduced expression of RNF8, MOF, H4Ac and H4K16Ac in round spermatids of KI mice. Absence of phosphorylated GRTH impairs UBE2J1, RNF8 and MOF-dependent histone ubiquitination and acetylation essential for histone replacement, chromatin condensation and spermatid elongation during spermiogenesis.